In vitro evaluation of Bixa orellana L. (Annatto) seeds as potential natural food preservative (2014)
ABSTRACT: This paper evaluates the in vitro antimicrobial and antioxidant effect of the ethanolic extract of annatto seeds (EEBS). Minimum inhibitory concentration (MIC) of the EEBS was determinate through microdilution method in 7 bacteria and 5 fungi strains, all of which are ATCC. The EEBS shows a wide antimicrobial action spectrum for both Gram positive and Gram negative bacteria, as well as for fungi with MICs between 0.5 and 2048 μg/ml. The most sensitive bacteria to the EEBS effect were Bacillus cereus, Staphylococcus aureus and Lactobacillus plantarum; while, Pseudomonas aeruginosa and Listeria monocytogenes showed greater resistant against it. Yeast and moulds were more sensitive to EEBS than bacteria, with MICs ranging from 512 to 0.5 μg/ml, where Saccharomyces cerevisiae was the most resistant yeast against the extract and Penicillium chrysogenum the most sensitive. On the other hand, nisin (positive control) showed a strong inhibition of growth for Gram positive bacteria and lower capacity against Gram negative had no capacity against fungi. Besides the broad antimicrobial action, EEBS showed an anti-radical capacity at concentrations lower than MIC at the found values. These results demonstrate the antimicrobial and antioxidant potential of the EEBS, that can possibly make this extract a new alternative for natural food conservation.